(untitled) (Bangladesh Journal of Medical Science, 2019)
Background and objective: Marginal or segmental resection of bone are often required for tumor removal in oral squamous cell carcinoma patients to secure adequate margin. The present study aims to evaluate the surgical outcome and post-operative complication of both group of patients and also assesses the local control of the disease in the oral cavity. Methods: In this prospective study, 32 patients who were treated with marginal or segmental jaw resection for oral squamous cell carcinoma of the lower part of oral cavity was undertaken within September 2008 to August 2013.There were 9 males and 23 females with a median age of 40.5 years. Twenty patients underwent marginal and 12 patients had segmental resection of the mandible. Distribution of the subject by age, sex, primary site of lesion, pathologic tumor stage, presence of mandibular invasion, pathologic cervical lymph node stage and feature of post- operative complications were analyzed prospectively. Results: According to this study, the mandible was involved in 83.3% of patient with segmental resection and 15% of patients with marginal resection. Buccal mucosa was mostly involved site in marginal group (60%) and retro molar trigon was highly involved site with segmental group (41.7%). In marginal group 30% cases was involved with stage1 and 70% was stage2; in segmental group 25% cases were stage2 and 67.7% were stage3. Statistically significant difference was exist in pathological cervical node stage(p<0.05). Mandibular invasion was significantly more in segmental group (p<0.05). Soft tissue surgical margins were positive in 4 patients (20%) in the marginal group and in 3 patients (25%) in the segmental group. Negative neck lymph node was found in 20 (63%) cases and positive neck node was found in 12 (37%) cases, of which four patients, including 2(15%) cases in the marginal group and 2(8.3%) cases in the segmental group was died. Trismus and mastication problems were found higher in segmental than marginal resection group. Conclusion: Marginal resection of mandible is effective for patient with oral squamous cell carcinoma in the early stage. Post-operative outcome and local control of disease in segmental group were slightly higher than marginal group. Positive surgical margin status and bone invasion was found as the most important predictor of local control of the diseases in patient with oral squamous cell carcinoma. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.801-807